Nhân tố ảnh hưởng nhận thức rủi ro của nông hộ sản xuất trái cây hàng hóa tại tỉnh Sơn La, Việt Nam - Hồ Văn, Bắc; Vũ Thị Hải, Anh; Hà Minh, Tuân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Agricultural production toward the oriented market is generally exposed to a variety of risks that may lead to income fluctuations. Correct identification of risk varieties will be a very important base for making good management decisions to minimize their negative effects. The research result indicated 14 risk sources that may affect the agricultural production of fruit farmers in the study area. Specifically, seedling quality, climate variability, disease, and pest issues are most serious as single risks by fruit farmer’s perception. Moreover, the result showed several socio-economic factors that have significant impacts on risk perception of farmers. Notably, accessing agricultural extension service and credit sources are found to reduce worries and risk perception. In addition, the findings also suggest possible policy intervention to minimize negative influences of risk sources on farmer’s agricultural production.
Keywords: Linear regression; Agriculture; Risk perception; Principal component analysis